Does an Optimal Relationship Between Injury Risk and Workload Represented by the “Sweet Spot” Really Exist? An Example From Elite French Soccer Players and Pentathletes - Sedeaud, Adrien; De Larochelambert, Quentin; Moussa, Issa; Brasse, Didier; Berrou, Jean-Maxence; Duncombe, Stephanie; Antero, Juliana; Orhant, Emmanuel; Carling, Christopher; Toussaint, Jean-Francois (Frontiers in Physiology, 2020)
Objective: to examine the relationships between the occurrence and severity of injuries using three workload ratios (ACWR, EWMA, REDI) in elite female soccer players and international male and female pentathletes. Materials and Methods: Female soccer players in the U16 to U18 national French teams (n=24) and international athletes (n=12, 4 women and 8 men) in the French modern pentathlon team were monitored throughout an entire season. The Acute Chronic Workload Ratio (ACWR), the Exponentially Weighted Moving Averages (EWMA), and the Robust Exponential Decreasing Index (REDI) were calculated for internal load by the ROE method in soccer and external load in pentathlon. The occurrence and severity of injuries (determined according to time-loss) were quantified in the sweet spot zone ]0.8; 1.3] and compared to the other zones of load variation: [0; 0.8], ]1.3; 1.5], ]1.5; +∞], using the three ratios. Results: Over the study period, a total of sixty-six injuries (2,75 per athlete) were reported in the soccer players and twelve in pentathletes (1 per athlete). The cumulative severity of all injuries was 788 days lost in soccer and 36 in pentathlon: respectively, 11.9 days lost per injury in soccer player and 3.0 per pentathlete. The mean values across the three methods in soccer showed a higher number of injuries detected in the [0; 0.8] workload ratio zone: 22.3 ± 6.4. They were 17.3 ± 3.5 in the sweet spot (]0.8-1.3] zone) and 17.6 ± 5.5 in the ]1.5; +∞] zone. In comparison to the [1.5; +∞] zone, soccer players reported a higher number of days lost to injuries in the presumed sweet spot and in the [0-0.8] zone: 204.7 ± 28.7 and 275.0 ± 120.7 days, respectively. In pentathletes, ten of the twelve injuries (83.3%) occurred in the presumed sweet spot. REDI was the only method capable of tracking workloads over all-time series. Conclusion: In the present cohort of elite soccer players and pentathletes, acute chronic workload calculations showed an association with injury occurrence and severity but did not provide evidence supporting existence of a sweet spot diminishing injury risk.